The Challenge of Sustainability : Linking Politics, Education and Learning - Wade, Ros; Atkinson, Hugh (Hugh Parker) (Book collections on Project MUSE., 2015)
This timely and accessible book explores the links between politics, learning and sustainability. Its central focus is the future of people and the planet itself. The challenges that we face in combating climate change and building a more sustainable world are complex and the book argues that if we are to successfully meet these challenges we need a fundamental change in the way we do politics and economics, embedding a lifelong commitment to sustainability in all learning. The book will be important reading for academics and students in a variety of related subjects, including politics, public policy, education, sustainable development, geography, media, international relations and development studies. It will also be a valuableresource for NGOs and policy makers.